The Billotron: a way to experimentally apprehend the subatomic world. (19th June 2015) - Chapon, A; Gibelin, J; Lopez, O; Cussol, D; Durand, D; Desrues, Ph; de Préaumont, H Franck; Lemière, Y; Perronnel, J; Steckmeyer, J C
Abstract: The Billotron is a device designed and built by the LPC Caen to illustrate the methods with which physicists are able to study the basic structure of matter, in particular the nucleus of the atom.